Pengaruh Keberagaman Produk Dan Persepsi Harga Terhadap Keputusan Pembelian Sepeda Ontel Di Toko Agung Jombang - Asnawi; Moch Heru Widodo; Stevanus Gatot Supriyadi (Efektor, 2022)
The purpose of this study was to determine the effect of product diversity and price perceptions on purchasing decisions for ontel bicycles at the Agung Jombang store. This research uses an explanatory research method and the analysis used is multiple linear regression. The sampling technique in this study used accidental sampling. Obtained a sample of 100 respondents where the collection using a questionnaire. The data analysis technique in this study used the validity test, reliability with Cronbach's alpha, classical assumption of simple regression, and t-test. From the results of the data analysis, the calculated t value is 0.084 < 1.66 table. this means that there is a significant influence between the variables of product diversity and price perceptions on purchasing decisions